IDENTIFIKASI KOMPONEN OBJEK WISATA BUKIT ARANG DI DESA LONUO, KECAMATAN TILONGKABILA, KABUPATEN BONE BOLANGO, PROVINSI GORONTALO - Hendra, Hendra (Universitas Negeri Makassar, 2022)
This study aims to analyze the tourism development of Bukit Arang in Lonuo Village, Tilongkabila District, Bone Bolango District, Gorontalo Province based on 4 components namely; attractions, accessibilites, amenities, activitas.activity. The research location is at Arang Hill, Lonuo Village, Tilongkabila District, Bonebolango District, Gorontalo Province. The data used in this study include primary data from field observations and secondary data from statistical data, books and scientific articles. Data collection uses two techniques, namely observation and documentation. The data analysis technique used in this study is a qualitative descriptive analysis technique by providing a clear and objective description of the components of the Bukit Arang tourist attraction. Based on research, Bukit Arang tourism is located in the regency capital, but has not received attention for tourism development and most of it is still managed traditionally. Awareness of visitors and the surrounding community regarding environmental preservation needs to be increased so as to minimize environmental and aesthetic problems. It is hoped that the local government will pay more attention to the development and improvement of the Bukit Arang tourist area so that it can become a mainstay destination in Bone Bolango Regency.